Jhumur Song: A Geo – Environmental Analysis: Exploring the Social and Environmental Dimensions of Jhumur Song (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Folk songs originate from the growth and evolution of the people, their every day struggle for life and the various geo- environment as well as socio-environment they belong to. The various lifestyle of the people in various sets of geo-environmental conditions gives birth to various forms of folk songs. Jhumur folk songs are a type of primitive musicals practiced by the people of western part of the states of Bengal as well as the parts of Orissa and Jharkhand. Jhumur is a typical form of folk art includes both songs and dance. Geography as a branch of social science can study the music and interpret the social and cultural life pattern of the people. Every form of folk songs are basically songs conveying something abut the way of life. They are the result of the human environment relationship. So, if we want to interpret the folk music in the light of geographical thought we should accept the concept of environmental determinism.